2022
DOI: 10.1016/j.ijregi.2022.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-SARS-CoV-2 antibodies in a population living in Bomassa village, Republic of Congo

Abstract: Objectives : As limited data are available from Central Africa, the aim of the present study was to evaluate the anti-SARS-CoV-2 Ab prevalence in indigenous residents, in Bomassa, a village located in the Sangha Region in the Republic of Congo. Methods : Plasma and oropharyngeal swabs samples were collected from 304 healthy adult individuals, randomly recruited in May 2021 before vaccine introduction in the area. In addition, 82 plasma samples from the same area in 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
5
8
2
Order By: Relevance
“…We noted a predominance of IgG (24.40 %) compared to IgM (20.62 %). Similar trends have already been reported with higher IgG level in the general population in USA [31], Cameroon [7], [32], [33], [34], Congo [35], India [36] and Brazil [37] as well as in students in Spain [38]. In fact, experience earned from the kinetics of antibody response from other viral infections taught us that unlike IgM that appears in the acute phase of infection, IgG is the marker of the chronic infection and should appear later on in greater amount.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We noted a predominance of IgG (24.40 %) compared to IgM (20.62 %). Similar trends have already been reported with higher IgG level in the general population in USA [31], Cameroon [7], [32], [33], [34], Congo [35], India [36] and Brazil [37] as well as in students in Spain [38]. In fact, experience earned from the kinetics of antibody response from other viral infections taught us that unlike IgM that appears in the acute phase of infection, IgG is the marker of the chronic infection and should appear later on in greater amount.…”
Section: Discussionsupporting
confidence: 87%
“…Four serological profiles were identified: 12.71% IgM-/IgG+, 11.68% IgM+/IgG+, 8.93% of IgM+/IgG-, 66.67 % of IgM-/IgG-. Similar results have been reported in Congo [35], in the USA [31], and in Cameroon [32], [33] with a sample size of 684, 368, 291 and 971 respectively. No association has been found between serological profiles and all the socio-demographic characteristics.…”
Section: Discussionsupporting
confidence: 87%
“…A serosurvey in six districts of Zambia showed that the case ascertainment rate was only one reported case per 92 actual infections, or 1·1%. 183 Similar findings apply to other countries—such as the Republic of the Congo, 184 the Democratic Republic of the Congo, 185 Malawi, 186 and Kenya 187 —suggesting that up to 80% of the population had already been infected by COVID-19 before the arrival of the omicron variant.
Figure 10 Estimated cumulative infections and estimated daily infections in the African region, Feb 4, 2020–May 31, 2022 Data from the Institute for Health Metrics and Evaluation, accessed May 31, 2022.
…”
Section: Section 2: a Review Of The Global Regional And National Resp...mentioning
confidence: 60%
“…We aimed to assess the neutralizing capacity induced by vaccination and natural infection by using a standardize commercial surrogate virus neutralization test (sVNT) [17]. The sVNT has been designed as a powerful alternative to the conventional plaque reduction neutralization test (PRNT) to measure neutralizing antibodies post-infection to SARS-CoV-2 [19][20][21][22], and in vaccinated individuals [23][24][25]. In addition, the design of the GenScript sVNT ELISA is adapted to determine the difference in binding inhibition to compare vaccines and infecting SARS-CoV-2 variants antibody responses.…”
Section: Discussionmentioning
confidence: 99%